A Systematic Review on Text-based Communication of Women’s Language - Widarti, Yanuar Yohana (Lingual Journal of Language and Culture; Vol 18 No 1 (2025): Lingual: Journal of Language and Culture, 2025)
Text messaging is one of the most sought topics in exploring the impact of gender-based language in non-verbal communication. Some elements in text messaging include symbols (emoticons and emojis), word expansion, curse words, capitalization, and other linguistic alterations that are reviewed as the top discriminators of the two genders. This study exposes on several previous studies on how women utilize and create new meanings of text-based communication features to compensate for the absence of non-verbal communication. This current study uses a qualitative method, adopting a literature review approach to select previous research papers and books, including journal articles and books. The present review highlights the finding that women’s language incorporates lexical and non-lexical linguistic features as tools to convey emotional nuances effectively. Future research on how men and women perceive expressive features is suggested.